2007
DOI: 10.1039/b700105n
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the dialdehyde glyoxal in workroom air—development of personal sampling methodology

Abstract: The dialdehyde glyoxal (ethanedial) is an increasingly used industrial chemical with potential occupational health risks. This study describes the development of a personal sampling methodology for the determination of glyoxal in workroom air. Among the compounds evaluated as derivatizing agents; N-methyl-4-hydrazino-7-nitrobenzofurazan (MNBDH), 1,2-phenylenediamine (OPDA), 1-dimethylaminonaphthalene-5-sulfonylhydrazine (dansylhydrazine, DNSH) and 2,4-dinitrophenylhydrazine (DNPH), DNPH was the only reagent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Sample recovery was determined by spiking 1 µg of glyoxal and methylglyoxal onto DNPH cartridges -recoveries were 96 ± 0.3 % for glyoxal and 111 ± 8 % for methylglyoxal. The degree of derivatisation was examined in these spiked cartridges to ensure both carbonyl groups in the glyoxal and methylglyoxal molecules had reacted with the 2,4-DNPH (Wang et al, 2009;Olsen et al, 2007). Analysis of samples that had been extracted within the last 24 h showed a second smaller peak, indicating that ∼ 5 % of the glyoxal had reacted to form mono-derivatives rather than bis-derivatives (e.g.…”
Section: Dnph Cartridges and Hplc Analysismentioning
confidence: 99%
“…Sample recovery was determined by spiking 1 µg of glyoxal and methylglyoxal onto DNPH cartridges -recoveries were 96 ± 0.3 % for glyoxal and 111 ± 8 % for methylglyoxal. The degree of derivatisation was examined in these spiked cartridges to ensure both carbonyl groups in the glyoxal and methylglyoxal molecules had reacted with the 2,4-DNPH (Wang et al, 2009;Olsen et al, 2007). Analysis of samples that had been extracted within the last 24 h showed a second smaller peak, indicating that ∼ 5 % of the glyoxal had reacted to form mono-derivatives rather than bis-derivatives (e.g.…”
Section: Dnph Cartridges and Hplc Analysismentioning
confidence: 99%
“…Bloom e f a1 (1979) surveyed a large number of Tasmanian animals and reported that the livers of birds and whole fish contained 0 to 18.3 and 0 to 6.0 mg/kg dieldrin respectively. Eleven of 34 water rat livers from the Murrumbidgee irrigation a r e a contained 0.01 to 0.09 mg/kg dieldrin in a survey by Olsen and Settle (1979) . Olsen et a1 (1980) detected a mean of 0.01 mg/kg dieldrin (range 0 to 0.34) in wings of black duck from 2 of 10 sites in Victoria and New South Wales.…”
Section: Discussionmentioning
confidence: 99%
“…While primary emissions, including wind-blown sea salt, make a large contribution to aerosol mass in the remote marine boundary layer (MBL), organic carbon can make a significant contribution to the mass of submicron marine aerosol in the more biologically active summer months (O'Dowd et al, 2004;Facchini et al, 2008a;Sciare et al, 2009;Ovadnevaite et al, 2011b). This organic carbon may be primary organic matter, including polymer microgels, viruses, bacteria, colloids and organic detritus, directly transferred from bulk water and the sea surface microlayer (SML) of the ocean to the atmosphere during bubble burst (Orellana et al, 2011;Facchini et al, 2008b). The organic carbon may also comprise secondary aerosol, formed from the oxidation of gas phase oceanderived volatile organic compounds (VOCs) such as DMS, isoprene and monoterpenes (Shaw et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of organics on cloud condensation nuclei (CCN) activity of marine aerosol in general appears to be highly variable, and investigations have mostly focused on primary organic aerosol (Ovadnevaite et al, 2011a;Meskhidze et al, 2011;Orellana et al, 2011;Westervelt et al, 2012;Topping et al, 2013). The contribution of DMS oxidation products to the CCN population over the remote Southern Ocean has been well established (Korhonen et al, 2008;Ayers and Gras, 1991); however, an understanding of the contribution of other secondary aerosol species, such as isoprene and monoterpene-derived SOA, to the CCN activity of marine aerosol is still emerging.…”
Section: Introductionmentioning
confidence: 99%